Práticas de contabilidade gerencial e fatores contingenciais em Agroindústrias Paraibanas - Barreto, Kamilla Alves (2019)
The objective of this study is to investigate the relation of contingency factors in the adoption of management accounting practices in the agroindustrial sector of the state of Paraíba-PB. As a methodology was used a survey through a structured questionnaire, with open and closed questions made by the researcher in an interview with the representatives of the enterprise investigated, obtaining as a sample thirty-two agroindustries. The questionnaire was composed of 84 questions, divided into 4 blocks, in which the respondent was asked to select among the assertions that best meets their perception about the topic. Data analysis was done through descriptive statistics from frequency observation, inferential correlation analysis and Cluster analysis using statistical software and the Cramer V test, with a significance level of 5%. As results, it was possible to perceive that the management of the companies surveyed is more related to the use of traditional practices. The practices of cash flow, break-even, analysis of product profitability and profitability of the segment, classified as information for decision making, stand out among the practices with the highest perception of adoption. The Balanced Scorecard and the Economic Value Added (EVA) were among all the managerial accounting practices, the ones which presented the lowest rate of adoption. It was noticed the increase in the adoption of management accounting practices in agroindustries that are inserted in stable environments, possessing high technology of medium and large size, with functional structure and strategy focused on differentiation. The adoption of traditional practices prevails in the different clusters, however, the levels of adoption of modern practices in groups of agroindustries inserted in more stable, high technology or larger environments are raised.